Studying Linguistic and Cultural Contact in Borneo: Prospects and Challenges - Antonia Soriente (Antropologia)
In the variegated landscape of languages and cultures of Borneo, the study of languages is a powerful tool to shed light on the intricate history of relations that has long been  obscured by the polarization between ‘Dayak’ and ‘Malay’. This article looks at some of the features of Lebu’ Kulit Kenyah, Penan Benalui, Punan Tubu’ and Ma’ Pnaan (Punan Malinau/Segah) languages to clarify the linguistic and cultural affiliations among groups that were otherwise lumped together in vague classifications. It demonstrates what is to follow: according to a number of phonological, morphological and lexical evidence, and other historical evidence, Lebu’ Kulit has to be listed among the Kayanic languages. Penan Benalui, like the other Penan languages, is not a Kenyah language, whereas Punan Tubu’, despite the alleged cultural and social similarity with other Punan groups, cannot be classified within the Penan branch nor with otherPunan languages. Ma’ Pnaan or Punan Malinau/Segah is not a Punan language and is linguistically classified within the Kayanic branch of the Kayan-Kenyah subgroup